Banking Control and its Role in Managing Financial Crises in the Arab Countries: The COVID-19 Crisis As A Model - زوايدية, أفراح; خوالد , أبوبكر; بوزرب , خير الدين (Finance and Business Economies Review, 2021)
This research aims to highlight the importance and role of banking control in managing and facing financial crises in general and the crisis resulting from the Corona pandemic in particular. Hence and to achieve this goal, we have relied on the descriptive and analytical approach. A basic conclusion was reached that the Arab monetary and control authorities have taken a considerable set of measures to contain the crisis, most notably: employing monetary policy tools, adopting significant economic stimulus packages, developing e-banking and modernizing payment methods, postponing payment of dues and bank evaluation processes, supporting startups and SME’s, etc. This research was concluded with a set of important recommendations that would activate the role of Arab banking control agencies in facing the economic and financial repercussions of the current global health pandemic (Covid-19).